Comparative study of arabic learning materials in traditional and modern pondok pesantren in North Sumatera, Indonesia - Cecep Farhani; Irfan Hania; Maksudin Maksudin; Suteja Suteja (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This study aims to compare the Arabic materials in the traditional Pondok Pesantren Al-Ansor and the Pondok Pesantren Al-Hasyimiyah Darul Ulum in North Sumatera. It is qualitative descriptive and comparative field research. Observation, interviews, and documentation were utilized to collect data for this study. This study's validity is examined using a triangulation of data sources. Data reduction, data presentation, and conclusion are the three phases of the data analysis technique. This studyâ€™s data analysis is inductive, with the researcher actively seeking for data, examining, analyzing, interpreting, and deriving conclusions from the observed phenomena. This study indicates that traditional Pondok Pesantren Al-Ansor and Pondok Pesantren Al-Hasyimiyah Darul Ulum Arabic language learning materials have similarities and differences. In the form of qawÄâ€™id, the material aspect of anÄÅ›ir al-lugah is comparable. The distinction is whether the Arabic material is taught through a program or not, and the learning outcomes that result. The Arabic language material on the mufradÄt and aá¹£wÄt learning aspects are not explicitly stated in the learning program at Pondok Pesantren Al-Ansor as a traditional pondok pesantren, but the qawaid learning material aspect is the primary focus at Ponpes Al-Ansor. In terms of mufradÄt and aá¹£wÄt learning materials, Pondok Pesantren Al-Hasyimiyah produces students with superior kalÄm and istimÄâ€™ skills. The qawÄâ€™id material aspect, meanwhile, is not a priority program because learning is limited to what is in the textbook.